The Survivorship Sleep Program (SSP): A synchronous, virtual cognitive behavioral therapy for insomnia pilot program among cancer survivors. Issue 7 (16th December 2021) - Hall, Daniel L.; Arditte Hall, Kimberly A.; Gorman, Mark J.; Comander, Amy; Goldstein, Michael R.; Cunningham, Tony J.; Wieman, Sarah; Mizrach, Helen R.; Juhel, Brooke C.; Li, Raissa; Markowitz, Alexandros; Grandner, Michael; et al.
Abstract : Background: For cancer survivors, insomnia is prevalent, distressing, and persists for years if unmanaged. Cognitive behavioral therapy for insomnia (CBT‐I) is an effective treatment yet can be difficult to access and may require modification to address survivorship‐specific barriers to sleep. In this 2‐phase study, the authors adapted and assessed the feasibility, acceptability, and preliminary effects of synchronous, virtual CBT‐I adapted for cancer survivors (the Survivorship Sleep Program [SSP]). Methods: From April to August 2020, cancer survivors with insomnia (N = 10) were interviewed to refine SSP content and delivery. From October 2020 to March 2021, 40 survivors were recruited for a randomized controlled trial comparing 4 weekly SSP sessions with enhanced usual care (EUC) (CBT‐I referral plus a sleep hygiene handout). Feasibility and acceptability were assessed by enrollment, retention, attendance, fidelity, survey ratings, and exit interviews. Insomnia severity (secondary outcome), sleep quality, sleep diaries, and fatigue were assessed at baseline, postintervention, and at 1‐month follow‐up using linear mixed models. Results: The SSP included targeted content and clinician‐led, virtual delivery to enhance patient centeredness and access. Benchmarks were met for enrollment (56% enrolled/eligible), retention (SSP, 90%; EUC, 95%), attendance (100%), and fidelity (95%). Compared with EUC, the SSP resulted in large, clinically significant improvements in insomnia severity (Cohen d = 1.19) that were sustained at 1‐month follow‐up (Cohen d = 1.27). Improvements were observed for all other sleep metrics except sleep diary total sleep time and fatigue. Conclusions: Synchronous, virtually delivered CBT‐I targeted to cancer survivors is feasible, acceptable, and seems to be efficacious for reducing insomnia severity. Further testing in larger and more diverse samples is warranted. Abstract : In this 2‐phase study, the authors adapt and assess the feasibility, acceptability, and preliminary effects of synchronous, virtual cognitive behavioral therapy for insomnia in cancer survivors compared with an enhanced usual care control. The adapted intervention is feasible, acceptable, and associated with large, clinically meaningful reductions in insomnia severity that are sustained at 1‐month follow‐up.